2014
DOI: 10.1002/agr.21373
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Hurdle Analysis of Demand for Powdered Milk: Evidence from Household Survey Data in an Urban Chinese Province

Abstract: The objective of this study is to explore the determinants of urban at-home consumption demand for powdered milk in Guangdong province from 2007 to 2009. A double-hurdle model is used in this analysis based on survey data. The data include 8188 household distributed in 15 cities and prefectures of Guangdong province. Major findings show that the income growth of urban household, an increase in the level of education of the householder, and the different age groups within the household all have positive effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…As an official statistical activity, the survey presents extensive information on demographic characteristics (i.e., household size and educational level), household incomes, living expenditure (including expenditure on different food and nonfood items), employment, housing, and asset ownership. This survey has been discussed in detail by Gould and Villarreal (2006), widely used in many recent studies on food demand (Fuller et al, 2004; Gould, 2002; Han & Chen, 2016; Liu & Chern, 2003; Wu et al, 2014). A total of 8818 urban households are randomly selected from 15 cities and prefectures in Guangdong province.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…As an official statistical activity, the survey presents extensive information on demographic characteristics (i.e., household size and educational level), household incomes, living expenditure (including expenditure on different food and nonfood items), employment, housing, and asset ownership. This survey has been discussed in detail by Gould and Villarreal (2006), widely used in many recent studies on food demand (Fuller et al, 2004; Gould, 2002; Han & Chen, 2016; Liu & Chern, 2003; Wu et al, 2014). A total of 8818 urban households are randomly selected from 15 cities and prefectures in Guangdong province.…”
Section: Datamentioning
confidence: 99%
“…Other factors such as family structure, cultural and economic forces are also likely to influence food consumption. Taking dairy demand as an example, Wu and Chen (2014) indicated that children and the elderly consume more dairy products than others in a given household because dairy products are considered nutritional supplements. Thus, these factors will be examined to analyze household dairy demand in an urban Chinese province.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban China has witnessed a rapid growth of dairy consumption from the 1990s to 2008 as a result of income growth, expansion of modern food retailers or marketing channels, the trend of higher education levels, and changes in urban lifestyles (Bai et al, 2008;Cheng et al, 2014;Fuller et al, 2006;Wu et al, 2014). According to the China Dairy Yearbook , the average annual dairy consumption of urban residents was 7.33 kg in 1995, which increased to 24.87 kg in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors affecting the food consumption demand, household income and food price are somewhat significant, while the effect of the family structure is also noticeable (Bai et al, 2010;Hovhannisyan and Gould, 2011;Zheng and Henneberry, 2011). Factors such as household ownership of a refrigerator, urban population size, and the characteristics of the geographic region also significantly affect food consumption (Huang and Rozelle, 1998;Yen et al, 2004;Gould and Villarreal, 2006;Bai et al, 2008;Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%